Development and Validation of a Tool to Explore Attitudes Towards meDication adHErence Using a Novel Self-Reported QuestionnairE (ADHERE-7) - Iva Bužančić; Mislav Balen; Dahna Arbanas; Slaven Falamić; Katarina Fehir Šola; Ana Galić Skoko; Mirna Momčilović; Ante Orbanić; Alena Tatarević; Maja Ortner Hadžiabdić (MDPI AG, 2024)
Despite the availability of various tools for measuring medication adherence, efficiently identifying non-adherence levels and reasons at the point of care remains challenging. Existing tools often lack the ease of use needed for practical clinical application. This study aimed to develop and validate a user-friendly tool to provide healthcare professionals with a concise yet comprehensive means of identifying adherence behaviors. The methodology consisted of two phases: tool items were first developed using the nominal group technique with healthcare professionals, followed by a cross-sectional pilot study involving community-dwelling adults in Croatia. Validation analysis indicated acceptable face and content validity and satisfactory criterion validity, with Attitudes towards meDication adHErence self-Reported questionnairE (ADHERE-7) scores correlating with both the self-reported five-item Medication Adherence Report Scale (MARS-5 tool) (ρ = 0.765; p < 0.001) and an objective measure of the proportion of days covered (PDC) from pharmacy prescription claims data (G = 0.586; p = 0.015). Construct validity revealed three factors: Aversion, Comfort, and Practical Non-Adherence, with Cronbach's alpha values of 0.617 for Aversion and 0.714 for Comfort Non-Adherence. The mean total score for ADHERE-7 was 26.27 ± 2.41 (range 17 to 28). This robust validation process confirms the ADHERE-7 tool as a reliable instrument for assessing medication adherence, addressing aversion, comfort, practical issues, and both intentional and unintentional nonadherence.